Current Rapid-Onset Antidepressants and Related Animal Models - Yan, Kuo; Chen, Yi-Bing; Wu, Jia-Rong; Li, Kuang-Dai; Cui, Yuan-Lu (Current Pharmaceutical Design, 2018)
Depression is a common mental disease, and it is one of the most crippling diseases in the world. Although current pharmacotherapies contribute to the treatment of depression, the high incidence of a partial responses or no responses, and delayed onset of the antidepressants, make many patients to experience unsatisfactory results from treatment. In view of the high suicide rate during the period of drug onset, it is critical to find antidepressant drugs with rapid onset for the treatment of depression. This paper mainly reviews some drugs that have rapid antidepressant effect and their mechanisms, including monoaminergic receptor drugs, glutamate receptor drugs, mammalian target of rapamycin (mTOR) signaling agonist, gamma-aminobutyric acid energy (GABAergic) agonist and drug combinations. In addition, we introduce several rodent models currently used to assess antidepressant onset in this review: chronic unpredictable mild stress (CUMS), forced swimming test (FST) and tail suspension test (TST), olfactory bulbectomy (OBX) and other models, which provide a methodological approach for assessing the rapid onset of antidepressant drugs.
Keywords: suspension test